Wage Differences between Incumbents and External Candidates - Wolter H.J. Hassink; G. Russo (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2003)
This paper compares the hourly wage of employees who change jobs within their firm with that of workers who are hired from other employers in the external labor market. We use a Dutch data set of about 45 thousand workers who are employed at 1,838 firms over in the years 1997 and 1998. We have the following empirical results: Workers who moved internally are in the higher segments of the wage distribution, relative to externally-hired workers. The difference in wage narrows a bit when we relate the workers with internal mobility to the hirees who were previously employed with another firm (job-to-job movement). We find that the difference in wage between internal candidates and external candidates from other employers disappears if we correct for the workers' observable characteristics. The empirical results indicate that on average there is no substantial wage difference between workers who make a transition between jobs within their firm and comparable workers who make a transition between firms in the external labor market.
Keywords: 330; Internal labor markets; External labor markets; Wages; Hiring; Risky Workers